Effects of collagen peptides from Micropterus salmoides skin on oxidative damage induced by cyclophosphamide in mice - Han, Mengyao; Zhang, Zhongshan; Li, Xinyue; Tong, Haibin; Xu, Zhiguo; Ding, Zikang; Yang, Anquan; Xie, Min; Wang, Xiaomei (Frontiers in Nutrition, 2022)
To investigate the protective effect of collagen peptide from Micropterus salmoides skin (CPMs) on oxidative damage induced by cyclophosphamide in mice. Balb/c female mice were divided into blank, model (cyclophosphamide, CTX), positive control (levamisole hydrochloride), and collagen peptide low-, medium-, and high-dose groups. The results showed that CPMs increase the body mass and immune-related organ indexes, such as liver and kidneys of immunosuppressed mice. The activities of ALT, AST, UA, BUN, and MDA in the liver and kidney tissues decreased significantly, while those of SOD and GSH-Px increased significantly. CPMs can relieve the pathological damage to immune organs. CPMs significantly increase the activities of IL-2, IgG, and TNF-α in serum and SOD activity, while the MDA content was decreased compared to the model group. CPMs can exert a protective effect on cyclophosphamide-induced oxidative damage and have application prospects in the field of health food.